Forensic genetic analysis of South Portuguese population with the six dye Powerplex® Fusion 6C - Vieira Da Silva, Cláudia; Afonso Costa, Heloísa; Porto, Maria João; Cunha, E; Corte Real, F.; Amorim, António (My University, 2019)
As an improvement in efficiency and in Human Discrimination Power, the new six dye multiplex kit PowerPlex® Fusion 6C System, by Promega, available for human identification can co-amplify 27 loci, in a single reaction, have been introduced in the last years with great success. This kit allows the amplification and detection of autosomal loci included in the expanded Combined DNA Index System CODIS, plus the loci Penta D, PENTA E and SE33 as well as Amelogenin for gender determination. Furthermore, this kit includes three Y –STRs (DYS391, DYS576 and DYS570), allowing allelic attribution in a total of 27 loci. This genetic markers extension satisfies not only CODIS but also European Standard Set recommendations. Thinking about continuous human migration movements, especially in a very cosmopolitan region like Lisbon and south of Portugal, and also, in keeping population studies and actualized STR databases we decided to update our previous studies. Our sample is composed of 600 unrelated individuals, from paternity testing with laboratory identity anonymised. DNA was extracted by Prep-n-go BufferTM(Thermo-Fisher Scientific). PCR amplification was performed with PowerPlex® Fusion 6C System, according to manufacturer’s guidelines. Fragment analysis was carried out in an Applied Biosystems® 3500 Genetic Analyser. Electrophoresis results were analysed with GeneMapper® ID-X v1.4. Allele frequencies and population statistics, including Hardy-Weinberg equilibrium p-values from exact test probabilities and forensic parameters were calculated with adequate software. In conclusion, our population information was updated in order to apply most recent data in our casework weight of evidence.
Poster apresentado no 28th Congress of International Society For Forensic Genetics (ISFG 2019), Praga, República Checa, 9-13 de Setembro de 2019
Keywords: Forensic DNA; PowerPlex ® Fusion 6C; Population Genetics; Portugal